2021
DOI: 10.1016/j.optom.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of angle Kappa on the optimal intraocular orientation of asymmetric multifocal intraocular lenses

Abstract: Purpose to evaluate the effects of kappa angle and intraocular orientation on the theoretical performance of asymmetric multifocal intraocular lenses (MIOL). Methods For a total of 21 corneal aberrations, a computational analysis simulated the implantation of a computationally designed MIOL. An image quality parameter (IQ) (visually modulated transfer function metric) was calculated for a 5.0-mm pupil and for three conditions: distance, intermediate, and near vision. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Although there has been an increasing interest in clarifying the possible predictive value of optical aberrations, angle kappa, and angle alpha in patient selection prior to MIOL implantation, only limited scientific evidence is available. The published results are sometimes contradictory or provide only moderately strong evidence [1,2,7,9,[11][12][13]19,20,23,24]. Additionally, the definition of angle kappa and alpha are not always the same in the literature, and measurement techniques often vary in different studies [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been an increasing interest in clarifying the possible predictive value of optical aberrations, angle kappa, and angle alpha in patient selection prior to MIOL implantation, only limited scientific evidence is available. The published results are sometimes contradictory or provide only moderately strong evidence [1,2,7,9,[11][12][13]19,20,23,24]. Additionally, the definition of angle kappa and alpha are not always the same in the literature, and measurement techniques often vary in different studies [25].…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of angle kappa in asymmetric segmented bifocal IOLs is a frequently discussed topic. [22][23][24] Yet, customized angle kappa implantation showed little impact on outcomes of the SBL-3 IOL, 25 the predecessor of the IOL evaluated in the current study. However, another small study found that pupil size might be of some relevance for this type of intraocular lens, and these findings deserve further investigation.…”
mentioning
confidence: 59%
“…Preoperative and postoperative quality of vision is a parameter that is rarely evaluated today, and the focus is placed mainly on the evaluation of visual acuity. The documented influence of the value of the above angles on vision has been the subject of many articles and confirms their indisputable importance in the process of qualification for implantation of premium class lenses, both concentric and asymmetric in their structure [1][2][3]. The evaluation of HOA generated by the cornea is one of the stable elements of qualification for surgery using a premium class lens [4].…”
Section: Introductionmentioning
confidence: 97%